The influence of study habits and self-concept on students' mathematical reasoning ability - Khairunnisa, Khairunnisa; Amry, Zul (Desimal: Jurnal Matematika, 2021)
This research aimed to determine the effect of study habits and self-concept on students' mathematical reasoning abilities in class VIII. This research is quantitative with the ex-post facto method. Sampling in this research using random sampling totaling 39 samples. The research instruments were two questionnaires totaling 30 items and an essay test totaling 3 items. The research results showed that there was an effect of study habits on students' mathematical reasoning abilities. There was no effect between self-concept on students' mathematical reasoning abilities. And there was an effect between self-concept and study habits on students' mathematical reasoning abilities. The conclusions of this research are learning habits does affect but self-concept doesn’t affect students' mathematical reasoning abilities, and self-concept and study habits affect the mathematical reasoning abilities of students in class VIII with a significant contribution of 25.9%.